Effect of Honey on levels of BMP-2 in post-extraction tooth sockets in Humans - Momina Khalid, Sehrish Zaffar, Muhammad Mutahir Mehdi, Mobin Riaz, Fatima Ikram, Maryam Saqib (Pakistan Journal of Medical & Health Sciences, 2022)
Background: In Pakistan, many people undergo tooth extractions every year due to various causes such as dental caries, periodontitis, and trauma. For a healthy alveolar bone after tooth extraction, some kind of intervention is always required. Honey can possibly help to improve bone healing after tooth extractions. Aim: To observe the effects of honey on bone healing of alveolar sockets after tooth extraction in humans. Method: It was an experimental study, conducted at Lahore general hospital over the period of 6 months. Twenty-four participants were included in the study through simple random sampling technique. After tooth extractions in both groups, honey was injected into extracted sockets of the experimental group while the control group was left as it was. Levels of BMP-2 were tested in saliva through the ELISA technique on days 1, 3, and 7 of tooth extraction. Results: In the control group, mean BMP-2 levels were 485.5± 52.63, 623.7 ±47.16 and 692.5± 11.86 while in the experimental group the mean values of BMP-2 were 494.3 ± 49.89, 703.6 ± 39.31 and 812.9 ± 34.40 at day 1, 3 and 7 respectively. The mean difference was calculated to be 8.75, 79.9, and 120.5. A significant difference (p-value <0.001) was noted in levels of BMP-2 between the experimental and control group on days 3 and 7. Conclusion: Raise in levels of BMP-2 in the experimental group when compared with the control group confirmed better bone healing. Hence, honey can be used to promote bone healing in post-extraction tooth sockets. This study can be used in future to improve bone quality and minimize ridge resorption after tooth extractions. Keywords: Bone morphogenetic protein-2 (BMP-2), Honey, Extracted Tooth sockets, bone healing, ELISA